English language teachers' differential treatment of the good, average and slow learners and their answering moves an interactional analysis - Florendo, Thelma E. 1930- (1986)
The main purpose of the study is to identify and describe a pattern of differential teaching towards the good, the average, and the slow English language learners and their response to such teaching in the Silliman University Elementary School.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: English language -- Study and teaching (Elementary) -- Philippines -- Dumaguete City; Teacher-student relationship